Predictors of Suicidal Ideation Across Deployment: A Prospective Study. Issue 9 (25th May 2015) - Cigrang, Jeffrey A.; Balderrama‐Durbin, Christina; Snyder, Douglas K.; Talcott, G. Wayne; Tatum, JoLyn; Baker, Monty; Cassidy, Daniel; Sonnek, Scott; Smith Slep, Amy M.; Heyman, Richard E.
<x xml:space="preserve">Abstract</x> Objective Concurrent and prospective predictors of suicidal ideation were examined in a sample of 318 United States Air Force Security Forces across a 1‐year deployment in Iraq and 6‐ to 9‐month follow‐up. Method Participants included 294 male and 24 female Airmen ranging in age from 18 to 46 years, predominantly (67%) Caucasian. Measures included self‐reports of postdeployment suicidal ideation, posttraumatic stress and depressive symptoms, alcohol use, combat experiences, relationship distress, social support, and postdeployment readjustment. Results Problem drinking before deployment prospectively predicted postdeployment suicidal ideation in univariate analyses. Depressive symptoms and problem drinking were significant independent predictors of postdeployment suicidal ideation. Findings demonstrated a ninefold increase in suicidal ideation among service members with even mild depressive symptoms if moderate problem drinking was also present. Conclusions Predeployment problem drinking may serve as a modifiable target for early intervention of suicidal ideation. Findings illuminate the compound risk of comorbid depressive symptoms and moderate problem drinking in predicting suicidal ideation.